Latitudinal pattern in community-wide herbivory does not match the pattern in herbivory averaged across common plant species - Elena L. Zvereva; Vitali Zverev; Vladimir A. Usoltsev; Mikhail V. Kozlov (Blackwell Publishing Ltd, 2022)
The latitudinal herbivory hypothesis (LHH) predicts that plant losses to herbivores decrease from low to high latitudes. Although the LHH is a community‐level hypothesis, it has been rarely tested with data on community‐wide herbivory, i.e. the percentage of annual production of foliar biomass consumed by insects from all plant species at a given site. Therefore, we asked whether community‐wide leaf herbivory follows the same latitudinal pattern as observed for an unweighted average of herbivory across common plant species.
We selected 10 study sites in boreal forests from 60 to 69°N along a 1,000‐km long latitudinal gradient in NW Russia. We measured relative foliar losses to insect herbivores in seven woody plant species (jointly comprising over 95% of the community‐wide above‐ground biomass) and estimated their current‐year foliar biomass. We averaged leaf herbivory for all seven species and calculated community‐wide leaf herbivory by weighting the relative foliar losses of each plant species against the contribution of that species to the annual foliar biomass production.
Leaf herbivory was five‐fold higher in deciduous species than in conifers. Latitudinal patterns in herbivory varied from a significant poleward decrease in all deciduous species to a significant poleward increase in Norway spruce. Herbivory values, averaged across seven plant species, decreased with latitude and followed the pattern observed in deciduous plants due to their higher foliar losses compared with conifers. By contrast, community‐wide herbivory did not change with latitude. This discrepancy emerged because the proportion of deciduous plant foliage in the community increased with increasing latitude, and this increase counterbalanced the simultaneous poleward decrease in losses of these species to insects.
Synthesis. The herbivory measured by averaging relative losses of individual plant species and community‐wide herbivory is likely to show different latitudinal patterns in various plant communities. The contributions of plant species to the total foliar biomass production should be taken into account in studies of spatial patterns of herbivory which test community‐level hypotheses. This approach may provide new insight into macroecological research on biotic interactions and improve our understanding of the role of insect herbivores in ecosystem‐level processes.